STUDI TEORITIS ADSORPSI DAN DISOSIASI MOLEKUL NH3 PADA PERMUKAAN Fe(111) PENTANUKLIR - , Gani Purwiandono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Theoretical study regarding the adsorption and dissociation of NH3 molecule on Fe(111) surface using DFT-B3LYP method with ECP and 6-311G** basis sets has been carried out. The aim of this research is to give the theoretical understanding about adsorption and dissociation of NH3 molecule on Fe(III) surface based on energetic parameter, bond length, electron population, vibration and orbital interaction. The result of theoretical calculation revealed that the ontop site is the interaction position with the minimum energy for the adsorption of NH3 molecule on Fe(III) surface. The analysis of electron population of the two composing molecular orbitals indicated that the transfer of electron has an important role in the mechanism of adsorption. The visualization of molecular orbital showed that the transfer of electron occurred in the electron pairs of the interacting orbitals. Concerning the adsorption mechanism and the overlapping of interaction orbitals, NH3 molecule provides the Highest Occupied Molecular Orbital (HOMO) as the interaction pair for the Lowest Unoccupied Molecular Orbital (LUMO) on Fe surface. All of the relevant empty orbitals on Fe surface show a significant role in the interaction result. Thus, the on-top site becomes the most effective interaction position for the adsorption of NH3 molecule. The dissociation of Fe-N in Fe5NH3 complex occurred homolitically through the formation of N radical. The dissociation of Fe-H occurred homolitically through the formation of H radical. The insignificant difference between oxidation state of N and H atoms and the higher homolytic N-H bond dissociation energy (compared to heterolytic dissociation) cause the adsorption mechanism of NH3 on Fe(III) model to occur through homolytic-dissociative chemisorption.